Ethical Objectives of Shariah and Their Impact on Contemporary Islamic Law - M. Munif; Mochammmad Syafiuddin Shobirin (International Journal of Law, 2025)
This article examines the role of maqāṣid al-sharī‘ah (the higher objectives of Islamic law) in shaping contemporary Islamic legal thought and practice. As Muslim societies navigate modern challenges such as governance, human rights, economics, and pluralism, the ethical framework provided by maqāṣid focusing on the protection of religion, life, intellect, lineage, and property offers a dynamic alternative to rigid textualism. Drawing on classical jurisprudential sources and contemporary scholarly developments, this study highlights how maqāṣid reasoning allows for more purposive, justice-oriented interpretations of Shariah. Through qualitative library research and case analysis, it is shown that maqāṣid-based approaches have influenced legislative reforms in several Muslim-majority countries, guided fatwas in minority Muslim contexts, and expanded the moral scope of Islamic law to address new ethical domains such as environmental responsibility and gender equity. While debates persist over methodological boundaries and interpretive authority, the study concludes that maqāṣid al-sharī‘ah provides an essential tool for aligning Islamic law with evolving societal needs while preserving its core ethical commitments.